LOGISTIC SYSTEM OF LOAD DELIVERY AND QUALITY OF ITS OPERATION - O. G. Drozdovskaya (Наука и техника)
The paper considers an opportunity for obtaining a competitive advantage by a transport and dispatch service company in the market of transport services while establishing a logistic system of load delivery. A model of delivery system, an universal scheme of system designing for every specific case are presented and also indices for evaluation of its operational quality are proposed in the paper.